FtSAD2 and FtJAZ1 regulate activity of the FtMYB11 transcription repressor of the phenylpropanoid pathway in Fagopyrum tataricum - Zhou, Meiliang (The New phytologist, 2017)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.